2021
DOI: 10.1016/j.esmoop.2021.100120
|View full text |Cite
|
Sign up to set email alerts
|

Discordance between immunochemistry of mismatch repair proteins and molecular testing of microsatellite instability in colorectal cancer

Abstract: Background: DNA mismatch repair system deficiency (dMMR) is found in 15% of colorectal cancers (CRCs). Two methods are used to determine dMMR, immunohistochemistry (IHC) of MMR proteins and molecular testing of microsatellite instability (MSI). Only studies with a low number of patients have reported rates of discordance between these two methods, ranging from 1% to 10%. Materials and methods: Overall, 3228 consecutive patients with CRCs from two centers were included. Molecular testing was carried out using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 52 publications
3
39
0
Order By: Relevance
“…Most tumors had MMR IHC tests (98.2%) and only 9 MSI/pMMR cases were identified (2.4%). These results were concordant with recent series ( Lindor et al, 2002 ; Watson et al, 2007 ; Fazzalari, 2017 ; Cohen et al, 2018 ; Jaffrelot et al, 2019 ; De Salins et al, 2021 ). A recent work showed that ∼6% of MSI cases retained mismatch repair protein expression and would consequently be missed by IHC testing alone, thereby hindering patient access to immunotherapy ( Hechtman et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Most tumors had MMR IHC tests (98.2%) and only 9 MSI/pMMR cases were identified (2.4%). These results were concordant with recent series ( Lindor et al, 2002 ; Watson et al, 2007 ; Fazzalari, 2017 ; Cohen et al, 2018 ; Jaffrelot et al, 2019 ; De Salins et al, 2021 ). A recent work showed that ∼6% of MSI cases retained mismatch repair protein expression and would consequently be missed by IHC testing alone, thereby hindering patient access to immunotherapy ( Hechtman et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Sensitivity and specificity of the Pentaplex panel range between 90 and 100% ( Xicola et al, 2007 ; Goel et al, 2010 ). Moreover, some studies have shown discordance between MMR IHC and MSI molecular testing, ranging from 1 to 10% ( Lindor et al, 2002 ; Watson et al, 2007 ; Jaffrelot et al, 2019 ; Guyot; De Salins et al, 2021 ). In our cohort, all tumors were initially determined as MSI using a robust test (Pentaplex panel) ( Suraweera et al, 2002 ; Wong et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies between MSI status and dMMR status exist even though both tests have high sensitivity and specificity. It is a rare phenomenon (1 to 2%), and most “false” discrepancies are due to common errors, for example poor quality of tissue sampling and/or poor quality of tissue fixation and staining [ 7 , 27 ]. Nevertheless, “true” discrepancies have been described when an inactive mutated MMR protein could remain expressed (missense mutation) but with a loss of function leading to a pMMR/MSI tumor [ 28 ].…”
Section: Consequences Of Mismatch Repair Deficiencymentioning
confidence: 99%
“…dMMR/MSI status dramatically increases tumor mutational burden [ 27 , 29 ]. In a study comparing the sequenced DNA of ten dMMR cancers with nine pMMR cancers (both colorectal and non-colorectal cancers), dMMR status resulted in a mean of 1782 somatic mutations per tumor as compared to 73 mutations per tumor in pMMR cancers [ 30 ].…”
Section: Consequences Of Mismatch Repair Deficiencymentioning
confidence: 99%
“…Both methods could be used, but some studies have shown discordances between MMR protein IHC and MSI molecular testing, with rates ranging from 1% to 10% [ 22 , 23 , 24 ]. Expert centers usually perform both tests.…”
Section: Criteria To Identify and Diagnose Lynch Syndromementioning
confidence: 99%